Fundamental Basis and Application of Cold-Room Project Design: A Turkish Case Study - Dalkilic, A. S.; Kurekci, N. A.; Kincay, O.; Wongwises, S. (SPRINGER HEIDELBERG, 2013)
In this paper, cold-room systems in Turkey's various regions were analyzed as case studies to demonstrate the application of the proposed model. They were also compared with each other in terms of the alteration of alternative refrigerants and insulation thickness and energy and exergy analyses of the cold rooms' refrigeration system. The coefficients of performance (COP), refrigerant charge rates, volumetric refrigeration capacity and capacities of each component of the refrigeration system for the refrigerants CFC-12, HCFC-22 and their alternatives, such as HFC-134A, HFC-404A, HFC-407C, HFC-410A and HFC-507, were determined by considering the effects of the main parameters of the performance analysis, such as refrigerant type, degree of subcooling, superheating and compressor efficiency. The first law efficiencies, exergy efficiencies and irreversibility rates were also obtained and discussed in this theoretical study. Based on the results of the energy analyses, all the alternative refrigerants have a slightly lower COP and require lower refrigerant charge rates than CFC-12 and HCFC-22 for condensation temperatures ranging from36-47 degrees C. The investigated large cities in Turkey have an evaporation temperature of -6 degrees C regarding the preserved product and various ambient temperatures of these largest cities of Turkey range from 31-42 degrees C in the case studies. Based on the results of the exergy analyses, the compressor has the greatest irreversibility, followed by the expansion valve, condenser and evaporator as the components of the refrigeration system.
Keywords: Cold room; Heat transfer; Refrigerant; Exergy; Case study; ADIABATIC CAPILLARY TUBES; REFRIGERATING SYSTEMS; HYDROCARBON MIXTURES; FLOW CHARACTERISTICS; REPLACE HFC-134A; PERFORMANCE; Science & Technology - Other Topics